RESEARCH NOTE Floral Bud Length as Morphological Predictor for Microspore Developmental Stage in Sturt’s Desert Pea (Swainsona formosa) - , Zulkarnain (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
This work was conducted to establish the relationship between microspore developmental stage and length of the floral bud in glasshouse-grown Sturt's desert pea, a native Australian legume.  The stages of microspore development were segregated into tetrad, early-uninucleate, mid-uninucleate and late-uninucleate.  The results showed that the stage of microspore development was highly dependent on the length of floral bud.  The tetrad stage lasted longer than early-, mid- or late-uninucleate stages.  The attempted induction of androgenesis in Sturt's desert pea using anthers from floral buds with similar size, as in the present work, was unsuccessful.  However, our work showed that the floral bud length can be used as a reliable predictor of microspore developmental stage in Sturt's desert pea.   Key words: Sturt's desert pea, Swainsona formosa, androgenesis, legume